CHARACTERIZATION OF PARALLEL SURFACES TO S- ? SURFACES IN HEISENBERG GROUP HEIS3 - Korpinar, Talat; Turhan, Essin (Editura Bibliotheca-Bibliotheca Publ House, 2012)
In this paper, we study parallel surfaces to S-alpha surfaces according to Sabban frame in the Heisenberg group Heis(3).
Keywords: Biharmonic curve; Heisenberg group; Sabban frame